2014
DOI: 10.1016/j.neubiorev.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent brain maturation and smoking: What we know and where we’re headed

Abstract: Smoking is a leading cause of mortality and morbidity worldwide. Smoking initiation often occurs during adolescence. This paper reviews and synthesizes adolescent development and nicotine dependence literatures to provide an account of adolescent smoking from onset to compulsive use. We extend neurobiological models of adolescent risk-taking, that focus on the interplay between incentive processing and cognitive control brain systems, through incorporating psychosocial and contextual factors specific to smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 312 publications
(355 reference statements)
2
99
0
3
Order By: Relevance
“…In particular, adolescents process salient incentives differently than adults, and have more trouble inhibiting responses. 36 The changing neurobiology of adolescents underscores the need for studying this population distinctly from adults, and creating a through body of knowledge specific to the variables that may differentially affect the smoking behavior of this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, adolescents process salient incentives differently than adults, and have more trouble inhibiting responses. 36 The changing neurobiology of adolescents underscores the need for studying this population distinctly from adults, and creating a through body of knowledge specific to the variables that may differentially affect the smoking behavior of this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescents, both the physical signs and negative affective states produced by withdrawal are lower than adults. Thus, it has been suggested that the strong rewarding effect of nicotine is a major contributing factor to enhanced tobacco use during adolescence [68][69][70][71]. In females, nicotine withdrawal produces an intense anxietylike behavior but similar physical signs as compared to males.…”
Section: Tobacco Use In Vulnerable Populationsmentioning
confidence: 99%
“…Nicotine has deleterious effects on the developing brain, harming neurodevelopment in utero and may have effects on brain development in adolescence [23,24]. Adolescence is a critical period of brain development with normal neurobiological changes that allow for increased risk-taking and heightened reactivity to short-term rewards rather than long-term goals.…”
Section: Risks Of Electronic Nicotine Delivery Systemsmentioning
confidence: 99%
“…Adolescence is a critical period of brain development with normal neurobiological changes that allow for increased risk-taking and heightened reactivity to short-term rewards rather than long-term goals. In animal studies, nicotine has been associated with cellular damage as well as acute and persistent changes in different neurobiological pathways within the developing adolescent brain [24]. Behaviorally, adolescents have been found to be more sensitive to nicotine and more likely to demonstrate dependence than their adult counterparts even with relatively low amounts of nicotine exposure and more likely to have continued use into adulthood [23,24].…”
Section: Risks Of Electronic Nicotine Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation